Corporate Governance In The U.S. Private Capital Markets: An Analysis Of The Certificates Of Incorporation Of Venture-Backed Privately Held Software Companies - Lyra, Zora (Revista Semestral de Direito Empresarial, 2024)
<div class="elementor-element elementor-element-262160f elementor-widget elementor-widget-jet-listing-dynamic-field" data-id="262160f" data-element_type="widget" data-widget_type="jet-listing-dynamic-field.default"> The corporate governance of any given company evolves over time and is affected by several factors, including its industry, place of incorporation, types of shareholders, whether it has gone public, and market standards. This paper aimed to identify patterns in the corporate governance of private software companies during the period in which they received investments from venture capitalists through a comparison of the content of their certificates of incorporation. The author also analyzed the clauses of a model certificate of incorporation provided by the National Venture Capital Association - NVCA and assessed whether a selected sample of companies followed the NVCA’s model and recommendations in terms of best practices of corporate governance. <div class="elementor-element elementor-element-d48b882 elementor-widget elementor-widget-jet-listing-dynamic-field" data-id="d48b882" data-element_type="widget" data-widget_type="jet-listing-dynamic-field.default">